2010
DOI: 10.1007/s11248-010-9416-3
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin transcription does not necessarily lead to efficient triggering of the RNAi pathway

Abstract: Previously, we had shown that stable expression of a hairpin RNA sharing homology with the coat protein (CP) of the Cucumber mosaic virus (CMV) (hpRNA(CMV)) produced CMV resistant Nicotiana tabacum plants. However, only 17% of the hpRNA(CMV)-expressing plants generated substantial amounts of siRNAs that mediated CMV resistance (siRNAs(CMV)). Here, we demonstrate that the transcription of a hpRNA(CMV) per se is not sufficient to trigger cytoplasmic and nuclear RNAi. A multiple-transgene copy line showed a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…2b), consistent with previous studies [6,14,51,52]. Moreover, as described in [53], the use of constructs expressing hairpin RNAs is not sufficient to ensure the production of siRNAs. Thus, not all such lines will produce siRNAs and not all the lines producing siRNAs will show resistance to the corresponding target viruses.…”
Section: Discussionsupporting
confidence: 89%
“…2b), consistent with previous studies [6,14,51,52]. Moreover, as described in [53], the use of constructs expressing hairpin RNAs is not sufficient to ensure the production of siRNAs. Thus, not all such lines will produce siRNAs and not all the lines producing siRNAs will show resistance to the corresponding target viruses.…”
Section: Discussionsupporting
confidence: 89%
“…In plants, RNAs that are inducers of PTGS can also mediate sequence-specific DNA methylation274649. We also observed that the double stranded RNA from the transgene hpIGR designed for inducing PTGS also triggered RdDM and methylated transgene sequences.…”
Section: Discussionmentioning
confidence: 59%
“…CHH methylation is mostly conducted by DRM2 and requires frequent methylation signals provided by the de novo methylation pathway43. Thus, methylated CHH is an indication for the ongoing de novo RdDM444546. Our data showed that the AYVV-resistant lines has, but susceptible lines lack, this competent CHH methylation and de novo RdDM signal.…”
Section: Discussionmentioning
confidence: 62%
“…A similar study by Dalakouras et al (2011) showed that siRNAs derived from a hairpin transgene construct triggered translational inhibition of that construct in tobacco. Although we only studied and confirmed a negative correlation between promoter methylation and construct expression for one of the constructs, a high extent of TGS is probably the main reason for the largely variable levels of resistance with the hairpin constructs against the three, targeted, nematodes that were observed in the current study.…”
Section: Discussionmentioning
confidence: 82%